Changes in Lake Rotcze catchment over the last 200 years: implications for lake development reconstruction - Kowalewski Grzegorz Andrzej (Limnological Review, 2013)
Based on archival cartographic sources, teledetection materials, and research results in the scope of history and environmental sciences, changes occurring in the catchment of Lake Rotcze and its close vicinity over the last two hundred years were analysed. The area of the catchment is dominated by moderately fertile minerogenic soils on which forest assemblages developed (poor hornbeamoak forest Tilio-Carpinetum and thermophilous oak forest Potentillo albae-Quercetum). The first trace of anthropopressure was a clearing at the southern shore of the lake, for agricultural use, established not later than at the turn of the 17th and 18th century. The forests were almost completely cleared in the first quarter of the 20th century, and transformed into cultivated land of the village of Grabniak. A large fragment of the catchment is occupied by peatlands, constituting the final stage of lake-peatland succession developed in the former bay of fossil Lake Uściwierskie of which Lake Rotcze constitutes the remains. During the 20th century, the peatlands were intensively drained. This resulted in their overdrying, and growing over with bushes and marshy forests. In the 20th century, Grabniak was an agricultural village. Over the last 25 years, it has turned into a recreation resort. The relatively short agricultural and settlement activity in the lake catchment, in comparison with other parts of Poland, makes the lake appropriate for palaeolimnological reconstruction in terms of looking for reference conditions (sensu WFD).